Marked Hematopoiesis Masquerading Multiple Bone Metastasis in a Lung Cancer Patient With Myelodysplastic Syndrome. (July 2015) - Imataki, Osamu; Uchida, Shumpei; Shiroshita, Kohei; Kida, Jun-ichiro; Uemura, Makiko
Abstract : Abstract: We diagnosed a 62-year-old man with lung cancer, well-differentiated squamous cell carcinoma, on the right upper lobe and left lower lobe. He had a history of myelodysplastic syndrome and refractory anemia with ringed sideroblasts diagnosed 5 years earlier. The patient's 18 F-FDG PET/CT for the clinical staging of lung cancer revealed accumulations of FDG in multiple bones including the rib bones, which strongly suggested multiple bone metastases. He underwent lobectomies and excision of the right fourth and fifth rib bones. The pathological findings of resected rib bones exhibited hypercellular bone marrow without excess of blasts.